Tropical forest susceptibility to and risk of fire under changing climate: a review of fire nature, policy and institutions in Indonesia - Herawati, H.; Santoso, H. (2011)
Forest fire is of both local and global concern. Large scale fires are not part of the natural disturbance of tropical rain forests but this threat has increased in the last few decades. Under global warming, Indonesia is projected to have higher temperatures and changes in rainfall patterns. Southern Indonesia is predicted to be drier whereas the north is likely to become wetter. Inter-annual climate variability associated with phenomena such as the El Niño Southern Oscillation may cause big decreases in rainfall. This paper reviews the nature and extent of fire problem and the effectiveness of the current policy and institutional provisions in Indonesia in addressing forest fires under projected future climate change. We then consider possible strategies for improving their effectiveness. The review results indicate that first, Indonesia has enacted a number of regulations and established various institutions to tackle forest and other wildfires, but these have proved ineffective. Second, under future climate change scenarios and current fire management practices, Indonesia's tropical rain forests could be more susceptible to fire. Third, effectiveness could be improved by addressing the underlying causes of fires, involving a wide range of stakeholders in formulating the regulations and enhancing law enforcement.